2020
DOI: 10.3389/fpsyg.2019.02944
|View full text |Cite
|
Sign up to set email alerts
|

Synchrony of Caresses: Does Affective Touch Help Infants to Detect Body-Related Visual–Tactile Synchrony?

Abstract: Bodily self-awareness, that is the ability to sense and recognize our body as our own, involves the encoding and integration of a wide range of multisensory and motor signals. Infants' abilities to detect synchrony and bind together sensory information in time and space critically contribute to the process of gradual bodily self-awareness. In particular, early tactile experiences may have a crucial role in promoting self-other differentiation and developing bodily self-awareness. More specifically affective to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 65 publications
0
8
0
Order By: Relevance
“…Besides playing an important role in bonding, these experiences of affective touch also allow infants to form associations between visual, tactile and proprioceptive bodily representations. Indeed, a recent study [58] found that five-month-old infants showed a preference for body-related visual-tactile synchrony when they received slow velocity CT-optimal affective touch, but not when they receive faster velocity non-affective touch. Although the relationship between this preference and the infants' previous experience with receiving affective touch was not investigated, these findings suggest that slow, caress-like touch, may facilitate the development of multisensory body representations in infancy.…”
Section: Box 1 Social Interactionsmentioning
confidence: 99%
“…Besides playing an important role in bonding, these experiences of affective touch also allow infants to form associations between visual, tactile and proprioceptive bodily representations. Indeed, a recent study [58] found that five-month-old infants showed a preference for body-related visual-tactile synchrony when they received slow velocity CT-optimal affective touch, but not when they receive faster velocity non-affective touch. Although the relationship between this preference and the infants' previous experience with receiving affective touch was not investigated, these findings suggest that slow, caress-like touch, may facilitate the development of multisensory body representations in infancy.…”
Section: Box 1 Social Interactionsmentioning
confidence: 99%
“…Videos were coded frame by frame using Datavyu software (Datavyu Team, 2014), widely used for coding infant data (e.g., Crespo‐Llado et al, 2018; Della Longa et al, 2020) at 30 frames per second. For both conditions, PCI‐FP and PCI‐Q, 5 min of interaction were coded, starting with the third and ending with the seventh minute of the interaction in each condition.…”
Section: Methodsmentioning
confidence: 99%
“…On the part of the infant, experiences of affectionate touch appear to support the development of bodily self-awareness, which in turn permits bodily attunement with their mothers ( Montirosso and McGlone, 2020 ). Touch may perform this role by facilitating the coordination of sensory processing across modalities: in a recent study, infants detected and showed a preference for synchronous visuo-tactile stimuli over asynchronous stimuli while experiencing CT-targeted gentle stroking, but not during other touch ( Della Longa et al, 2020 ). As interactional synchrony requires awareness of self and other, and takes place through coupled auditory, tactile, and visual signaling, affectionate touch may be a critical precursor to the infant’s detection of and participation in communicative rhythms.…”
Section: A Role For Touch In Parent–infant Interactional Synchronymentioning
confidence: 99%